Glaciers, gender, and science: A feminist glaciology framework for global environmental change research - Carey, Mark; Jackson, M.; Antonello, Alessandro; Rushing, Jaclyn (Progress in Human Geography, 2016)
Glaciers are key icons of climate change and global environmental change. However, the relationships among gender, science, and glaciers – particularly related to epistemological questions about the production of glaciological knowledge – remain understudied. This paper thus proposes a feminist glaciology framework with four key components: 1) knowledge producers; (2) gendered science and knowledge; (3) systems of scientific domination; and (4) alternative representations of glaciers. Merging feminist postcolonial science studies and feminist political ecology, the feminist glaciology framework generates robust analysis of gender, power, and epistemologies in dynamic social-ecological systems, thereby leading to more just and equitable science and human-ice interactions.
Keywords: approches et analyses; discipline; environnement; glaciologie; histoire et politique; intersectionnalité; point de vue situé; projet charge mentale; sciences; sciences de la terre; thématiques; études postcoloniales

Anishnaabe-Kwe, traditional knowledge, and water protection - McGregor, Deborah (Canadian Woman Studies, 2008)
26CANADIAN WOMAN STUDIES/LES CAHIERS DE LA FEMMEDans cet article, l’auteure partage ses expériences de travail sur les questions environnementales, particulièrement sur celles qui concernent l’eau. Comme mère, comme membre d’un clan, comme membre des Premières Nations et comme professeure, l’auteure se sent responsable du partage de ses connaissances. Cette réflexion est basée sur son travail avec les aînées et les tenants du savoir traditionnel en Ontario, surtout de celui qui se rapporte à l’eau. L’information part de deux projets majeurs dans lesquels elle a été impliquée.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; droit; droit de l'environnement; eau; environnement; féminisme autochtone; ontario; point de vue situé; pol4105; premier cycle; pédagogie; périodes historiques; régions géographiques; science politique et droit; sciences de l'éducation; thématiques; transmissions; écoféminisme; écoféminisme amérindien